2014
DOI: 10.1177/0891242413513495
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Attenuation of Barriers to Entrepreneurship

Abstract: Results are reported from a Latino immigrant entrepreneur needs assessment survey. The research project was conducted to identify barriers to business formation and continuation within the target population. A total of 171 surveys representing more than 200 businesses from 39 communities in 21 counties in western Arkansas were collected. Nearly 42% of respondents cited start-up capital as their biggest barrier with another 15% naming it as the second biggest barrier. Understanding government regulations and ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
(11 reference statements)
2
12
0
Order By: Relevance
“…In this study, almost all participants reported that information about business planning, marketing strategies, licensing and tax regulations, and financing was of most concern during their startup phase. This information deficit is consistent with other studies on Latinx immigrant business owners (Moon et al, 2014;Zarrugh, 2007).…”
Section: Access To Informationsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, almost all participants reported that information about business planning, marketing strategies, licensing and tax regulations, and financing was of most concern during their startup phase. This information deficit is consistent with other studies on Latinx immigrant business owners (Moon et al, 2014;Zarrugh, 2007).…”
Section: Access To Informationsupporting
confidence: 92%
“…A modified interview instrument developed by Moon et al (2014) was used to collect information from BIPOC business owners See Appendix 1. The instrument was written in English, translated into Spanish, and interpreted in Mandarin to Chinese business owners.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Female entrepreneurs with more educational attainment do not receive as great of a return, in terms of financial success, as do their male counterparts (Smith-Hunter, 2004). Latina entrepreneurs have smaller businesses compared to male entrepreneurs and face greater obstacles in obtaining financial capital (Moon and Farmer, 2014; Moon et al , 2014; Smith-Hunter, 2004). Furthermore, a recent literature review (Panda, 2018) indicated key constraints faced by female entrepreneurs in developing countries that included gender discrimination; work-family conflict; financial constraints; lack of infrastructural support; unfavorable business, economic and political environments; lack of entrepreneurship training, education; and personality-based constraints.…”
Section: Literature Reviewmentioning
confidence: 99%